Environmental DNA data provides taxa-specific insights into community differences across Reunion Island back-reef depressions - Dominique A. Cowart; Thomas Chevrier; Anne-Elise Nieblas; Jérémie Chanut; Aloïs Le Roux; Magali Duval; Tévamie Rungassamy; Serge Bernard; Sylvain Bonhommeau (Regional Studies in Marine Science, 2026)

Density distribution of the charismatic Kagu to guide conservation of endangered endemic rainforest species in New Caledonia - Jörn Theuerkauf; Yuji Okahisa; Gavin R. Hunt; Sophie Rouys; Mélanie Boissenin; Henri Bloc; David Ugolini; Vivien Chartendrault; Thomas Duval; Baptiste Angin; Frédéric Desmoulins; Nicolas Barré; et al. (Journal of Ornithology, 2026)
The Kagu ( Rhynochetos jubatus ) is an endangered endemic bird and emblem of New Caledonia, thus an ideal flagship species for conservation management and planning of protected areas on Grande Terre, the main island. We assessed the density distribution of Kagu by combining results of analyses at two spatial scales. At the local scale, we estimated density in two protected Kagu strongholds. At the island-wide scale, we modelled distribution using MaxEnt over the entire Kagu range on Grande Terre. We then combined these approaches to convert distribution probability into a density distribution. Proportion of rainforest and size of the largest rainforest patch within 250 m × 250 m raster cells were the main factors predicting Kagu distribution. Another important factor was distance to settlements, which is likely related to dog presence, the only significant predator of Kagu. The model identified nearly 2000 km 2 as habitat, which could potentially support over 27,000 Kagu. However, exluding the 5 km of sink habitat around settlements due to dog predation and applying a saturation of the population density at 23% ± 9%, which we observed in protected areas not managed for dogs, a realistic estimate of current Kagu numbers would be 3640 ± 1345. Only 12% of predicted Kagu habitat falls within protected areas, and only half of this protected area is under dog control. Moreover, only 30% of protected rainforest is situated on non-ultramafic soils, which are most suitable for Kagu and can support the highest densities. Numbers of Kagu and other endangered rainforest species could be significantly increased by establishing new protected areas combined with appropriate dog control. We recommend creating 250 km 2 of new protected areas in rainforest on non-ultramafic soils, which could potentially boost the Kagu population by 9000 individuals.

Deep genetic divergence underlies within-island eco-morphological variation in the endangered day gecko Phelsuma borbonica: implications for conservation - Josselin Cornuault; Mickaël Sanchez; Thomas Duval; Antoine Fouquet; Christophe Thébaud (Conservation Genetics, 2024)

A comprehensive multiplatform metabolomic analysis reveals alterations of 2-hydroxybutyric acid among women with deep endometriosis related to the pesticide trans-nonachlor - Tiphaine Lefebvre; Manon Campas; Komodo Matta; Sadia Ouzia; Yann Guitton; Gauthier Duval; Stéphane Ploteau; Philippe Marchand; Bruno Le Bizec; Thomas Freour; Jean-Philippe Antignac; Pascal de Tullio; et al. (Science of The Total Environment, 2024)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

An unprecedented bloom of Lingulodinium polyedra on the French Atlantic coast during summer 2021 - Kenneth Neil Mertens; Michael Retho; Soazig Manach; Maria Laura Zoffoli; Anne Doner; Mathilde Schapira; Gwenael Bilien; Véronique Séchet; Thomas Lacour; Elise Robert; Audrey Duval; Aouregan Terre-Terrillon; et al. (Harmful Algae, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Unusual blood profiles in the endemic Kagu of New Caledonia are not physiological - Roman Gula; Henri Bloc; Thomas Duval; Jörn Theuerkauf (Journal of Ornithology, 2020)
Previous research reported a unique haematological profile in the flightless Kagu ( Rhynochetos jubatus ). To verify this, we analysed blood of eight wild and four captive Kagu. The haematological profiles of our captive birds resembled those of the previously studied captive Kagu. Haemoglobin concentration, mean corpuscular haemoglobin concentration and mean corpuscular haemoglobin by far exceeded the highest levels recorded for birds. Conversely, the blood profile in wild Kagu fit in the range of other birds. We conclude that blood profiles of captive Kagu indicate a pathology, and that Kagu do not have fundamentally different blood characteristic than other endothermic vertebrates.

Isolation and characterization of twelve polymorphic microsatellite loci for investigating an extreme case of microgeographical variation in an island bird (Zosterops borbonicus) - Joris A. M. Bertrand; Ricardo García-Jiménez; Yann Bourgeois; Thomas Duval; Philipp Heeb; Christophe Thébaud; Borja Milá (Conservation Genetics Resources, 2012)

The role of immigration and in‐situ radiation in explaining blood parasite assemblages in an island bird clade - JOSSELIN CORNUAULT; ANAÏS BATAILLARD; BEN H. WARREN; AMÉLIE LOOTVOET; PASCAL MIRLEAU; THOMAS DUVAL; BORJA MILÁ; CHRISTOPHE THÉBAUD; PHILIPP HEEB (Molecular Ecology, 2012)
Parasite communities on islands are assembled through multiple immigrations and/or in‐situ diversification. In this study, we used a phylogenetic approach to investigate the role of such processes in shaping current patterns of diversity in Leucocytozoon , a group of haemosporidian blood parasites infecting whites eyes ( Zosterops ) endemic to the Mascarene archipelago (south‐western Indian Ocean). We found that this parasite community arose through a combination of multiple immigrations and in‐situ diversification, highlighting the importance of both processes in explaining island diversity. Specifically, two highly diverse parasite clades appear to have been present in the Mascarenes for most of their evolutionary history and have diversified within the archipelago, while another lineage apparently immigrated more recently, probably with human‐introduced birds. Interestingly, the evolutionary histories of one clade of parasites and Indian Ocean Zosterops seem tightly associated with a significant signal for phylogenetic congruence, suggesting that host–parasite co‐divergence may have occurred in this system.

Molecular characterization of AtNAM: a member of theArabidopsis NAC domain superfamily - Manuel Duval; Tzung-Fu Hsieh; Soo Young Kim; Terry L. Thomas (Plant Molecular Biology, 2002)

Phenolic compounds and antioxidant properties in the snow alga Chlamydomonas nivalis after exposure to UV light - Brian Duval; Kalidas Shetty; William H. Thomas (Journal of Applied Phycology, 1999)